1997
DOI: 10.1172/jci119279
|View full text |Cite
|
Sign up to set email alerts
|

20-Hydroxyeicosa-tetraenoic acid (20 HETE) activates protein kinase C. Role in regulation of rat renal Na+,K+-ATPase.

Abstract: It is well documented that the activity of Na

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
98
0
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(106 citation statements)
references
References 44 publications
7
98
0
1
Order By: Relevance
“…proximal tubular S2 and S3 segments), where, due to uncomplicated access to the systemic circulation, this eicosanoid could contribute to renovascular tone regulation and, ultimately, arterial blood pressure control. Furthermore, since the proximal tubule is where most electrolyte and water reabsorption occurs (1), the capacity of 20-HETE to potently inhibit Na ϩ /K ϩ -ATPase activity in this region of the nephron probably contributes to its known natriuretic and diuretic effects (4,62,74). In rats, CYP4A expression and 20-HETE formation have also been noted in renal microvessels (19,29,75), another proposed site where this eicosanoid influences vascular tone, autoregulation of renal blood flow, and/or tubuloglomerular feedback (9,10).…”
Section: -Hete Formation By Human Renal P450 Enzymesmentioning
confidence: 99%
“…proximal tubular S2 and S3 segments), where, due to uncomplicated access to the systemic circulation, this eicosanoid could contribute to renovascular tone regulation and, ultimately, arterial blood pressure control. Furthermore, since the proximal tubule is where most electrolyte and water reabsorption occurs (1), the capacity of 20-HETE to potently inhibit Na ϩ /K ϩ -ATPase activity in this region of the nephron probably contributes to its known natriuretic and diuretic effects (4,62,74). In rats, CYP4A expression and 20-HETE formation have also been noted in renal microvessels (19,29,75), another proposed site where this eicosanoid influences vascular tone, autoregulation of renal blood flow, and/or tubuloglomerular feedback (9,10).…”
Section: -Hete Formation By Human Renal P450 Enzymesmentioning
confidence: 99%
“…Inhibition of the synthesis of 20-HETE attenuates the vasoconstrictor response of renal arterioles to elevations in transmural pressure in vitro (16, 18) and autoregulation of renal blood flow and tubuloglomerular feedback responses in vivo (8,48). At the level of the renal tubules, 20-HETE inhibits sodium reabsorption in the proximal tubule and thick ascending limb of the loop of Henle (6,32,34,39).Previous studies indicated that the renal production of EETs and/or 20-HETE is altered in diabetes and in genetic and experimental models of hypertension (1,7,21,24,25,28,41). The release of 20-HETE in renal and peripheral blood vessels is stimulated by ANG II (5), phenylephrine (20a), endothelin (37), and serotonin (3).…”
mentioning
confidence: 99%
“…Inhibition of the synthesis of 20-HETE attenuates the vasoconstrictor response of renal arterioles to elevations in transmural pressure in vitro (16, 18) and autoregulation of renal blood flow and tubuloglomerular feedback responses in vivo (8,48). At the level of the renal tubules, 20-HETE inhibits sodium reabsorption in the proximal tubule and thick ascending limb of the loop of Henle (6,32,34,39).…”
mentioning
confidence: 99%
“…9 -11 Eicosanoids that inhibit tubular sodium transport are also produced by cytochrome P-450 (CYP 450) monooxygenase metabolism of arachidonic acid (AA); 20-HETE is the major metabolite of this pathway in mammalian kidney. This compound inhibits sodium transport at the proximal tubule Na ϩ -K ϩ -ATPase 12 and, most importantly, at the thick ascending limb NKCC. 13 The inhibitory action on the NKCC cotransporter is possibly mediated by impaired apical K ϩ -channel recycling of K ϩ .…”
mentioning
confidence: 99%